Determination of net energy content of dietary lipids fed to growing pigs using indirect calorimetry. (13th April 2018) - Li, Enkai; Liu, Hu; Li, Yakui; Liu, Ling; Wang, Fenglai; Li, Defa; Zhang, Shuai
Abstract: The objective of this experiment was to determine the NE content of different dietary lipids fed to growing pigs using indirect calorimetry. Thirty-six growing (initial BW: 41.1 ± 3.1 kg) barrows were allotted to 6 diets based on completely randomized design with 6 replicate pigs per diet. Diets included a corn-soybean meal basal diet and 5 test diets each containing 10% palm oil, poultry fat, fish oil, corn oil, or flaxseed oil at the expense of corn and soybean meal. During each period, pigs were individually housed in metabolism crates for 14 d, which included 7 d for adaptation to feed, metabolism crates, and environmental conditions. On day 8, pigs were transferred to the open-circuit respiration chambers and fed 1 of the 6 diets at 2.3 MJ ME/kg BW 0.6 /day. Total feces and urine were collected and daily heat production (HP ) was also calculated from day 9 to day 13. On the last day of each period (day 14), pigs were fasted and the fasting heat production (FHP ) was measured. The results show that the FHP of pigs averaged 809 kJ/kg BW 0.6 ·day −1 and was not affected by diet characteristics. The DE values were 35.98, 36.84, 37.11, 38.95, and 38.38 MJ/kg DM, the ME values were 35.79, 36.56, 36.92, 37.73, and 38.11 MJ/kg DM, and the NE values were 32.42, 33.21, 33.77, 34.00, and 34.12 MJ/kg DM, for the palm oil, poultry fat, fish oil, corn oil, and flaxseed oil, respectively. Based on our result, we concluded that the DE content of dietary lipid varied from 91% to 98% of its GE content, the ME content of dietary lipid was approximately 99% of its DE content, and the NE content of dietary lipid was approximately 90% of its ME content in growing pigs.